Jogada de craque? fatores críticos que levam empresas públicas a patrocinarem o esporte - Cunha, Vinicius de Faria (2012)
This dissertation aims to discuss sports marketing issues, emphasizing the role of Brazilian State-owned companies as sports supporters. There is still a lack of acknowledgment regarding their sponsorship policies and interests in doing so, and that is the gap this paper intends to fill. What critical aspects might be involved in the decision of State-owned companies to establish sports sponsorship? The author will carry out bibliographical research to gather some data on the returns from sports marketing. In addition to this, the BNDES and Eletrobras – two of the largest Brazilian publicly-owned companies – will be scrutinized to better understand patterns, concerns and goals related to their involvement with sport. The outcome, once generalized, will shed light on corporate sports marketing strategies, and, thus, the dissertation will accomplish its goals.